The Role of Production in Infant Word Learning. Issue 2 (September 2014) - Vihman, Marilyn May; DePaolis, Rory A.; Keren‐Portnoy, Tamar; Molnar, Monika; Sebastian‐Galles, Nuria
<x xml:space="preserve">Abstract</x> Studies of phonological development that combine speech‐processing experiments with observation and analysis of production remain rare, although production experience is necessarily relevant to developmental advance. Here we focus on three proposals regarding the relationship of production to word learning: (1) Articulatory filter: The hypothesis that children are influenced in noticing words in input speech by their resemblance to patterns they can produce has recently received experimental support. (2) Systematization and regression: It is proposed that the decline in accuracy that follows first‐word production is the consequence of an increase in systematicity (with renewed accuracy emerging only later). (3) Word‐production experience facilitates new word learning: Evidence that expressive vocabulary growth in itself facilitates new word learning supports the idea that knowledge is gradient, involving increases in stability and reliability with repeated exposure and use.